Pengaruh Job Satisfaction Terhadap Employee Performance Pada Perusahaan Penggilingan Tepung di Surabaya - Adi, Prayonne; Darmawan, Bryan; Gooier, Willy (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2023)
One of the factors that affect job performance is employee satisfaction with their work environment. This study aims to measure job satisfaction and job performance and test the correlation between the two variables using various measurement methods, including eNPS, ESI, Rating Scale Individu, and Individual Work Performance Questionnaire (IWPQ). The correlation between job satisfaction and job performance can be calculated using Scatterplot and Pearson Correlation. The eNPS measurement results show that employees gave a score of 6%, indicating a fairly good position for the company. The ESI score for employees is 72.8, which is a good result but still has room for improvement. Based on the Pearson Correlation calculation, the correlation value is 0.733, indicating a positive relationship between job satisfaction and job performance. Based on the research findings, some improvement ideas include increasing salary, sanitation, comfort in religious facilities, and room comfort.